Patterns of Interpersonal Violence Experience and Their Association with Mental Health and Substance Use Problems among Women with Incarceration Histories: A Multidimensional Longitudinal Study - Zhao, Qianwei (Journal of family violence, 2023)
PurposeResearch on the interpersonal violence experience among women with incarceration histories has primarily focused on the impact of discrete forms of victimization or used an additive measure of experiences. Few studies, however, have examined patterns of victimization among this population. The current study uses the Add Health data to explore patterns of interpersonal violence exposure among women with incarceration histories and examine the association between victimization patterns and mental health and substance use problems.MethodThe study sample included 418 women with incarceration histories. Latent class analysis was conducted to generate patterns of interpersonal violence victimization. Multivariate logistic regressions were then employed to examine group differences in mental health and substance use problems.ResultsFour distinct interpersonal violence patterns were identified among women with incarceration histories, characterized by high lifetime physical violence, high lifetime sexual and intimate partner violence, high childhood abuse, and low violence victimization. Multivariate logistic regressions revealed that “high lifetime sexual and intimate partner violence” experience was associated with higher odds of depressive symptomology, anxiety, suicidal ideation and attempt, and alcohol and illicit drug misuses compared to “low violence victimization.” Moreover, “high childhood abuse” experience was associated with higher odds of PTSD and marijuana and other illicit drug misuses than “low violence victimization.”ConclusionsFindings suggest using a multifaceted interpersonal violence assessment to understand violence victimization and related needs among women with incarceration histories. Future research is needed to explore whether violence victimization experience, incarceration, and substance use/mental health interact over their life course.